(untitled) (ALBACORE Jurnal Penelitian Perikanan Laut, 2026)
Light fishing are an essential piece of equipment for purse seine operations because they increase catch efficiency by drawing schooling fish with their phototaxis response. Nonetheless, variations in light design and operation significantly affect fishing productivity. The purpose of this study was to examine the fishing lights’ operational efficiency and construction features on the KM. Mutiara Sejati purse seine vessel that operates at the Bajomulyo Fishing Port in Central Java. Data was collected through organized interviews with the captain and crew, technical measurements of the lighting system, and direct field observations during ten fishing expeditions. According to the findings, the ship used a multi-light system with 40 units: 16 funnel lamps (corong), 16 galaxy lamps, 8 LED lamps, and 1 raft light. Before the net was deployed, illumination was progressively reduced using galaxy lamps, LED lamps, and finally funnel lamps to optimize fish aggregation. Fish were located using fish finders, and they were concentrated using raft light. According to the study, by keeping fish concentration close to the vessel, this sequential light operating strategy increased catch efficiency. These results offer purse seine fishermen useful advice on how to maximize fishing light operations and increase catch productivity. Key words: fish aggregating devices (FADS), light fishing, purse seine